Mandatory and Supervised Curricular Internship in Primary Health Care II - Municipality of Jaboatão dos Guararapes, state of Pernambuco (PE) - Guimarães Sampaio Trajano Dos Santos, Pedro; Cavalcanti de Lima Félix, Lucas; Travassos, Rosana Maria Coelho; Gonçalves Duarte, Marvin; Coelho de Ataíde Filho, Ailton; Scavuzzi Carneiro Cunha, Rodolfo; de Queiroz Marques Filho, Eudoro; Fonsêca da Silva, Hadassa; de Reis Melo Júnior, Paulo Maurício; Barreto Silva, Luciano (Brazilian Journal of Implantology and Health Sciences, 2025)
Objective: The objective of this experience report article is to report the experiences of two third-year dentistry students in a family health unit, reporting the conditions of the place, procedures that were observed, operation of the unit and the interprofessional relationship between the different professionals of the local. Methodology: A total of 8 visits to the USF were organized, visits that would be carried out to visualize the functioning of the unit, from the vaccination area, pharmacy, infirmary, medical care and mainly dental care. In addition, it was possible to see the daily interprofessional relationship between the health professionals of the unit, mainly the importance of community health agents in dental care. Results: During the internship, it was possible to visualize various dental procedures, such as: tooth extractions, restorations, sutures, fluoride applications and prophylaxis together with oral health education actions. It was also possible to visualize the functioning of the pharmacy, vaccination and which procedures the nursing area is able to perform within the conditions of the unit. Conclusion: The conclusion reached after the experience at the unit is that the unit is extremely important for the region, as the vast majority of patients seen by the local dentist receive health care only at that unit, where the majority do not have health insurance. In addition, the importance of the relationship between the community health agent and the dentist was seen, where patients only come to be seen by the surgeon if the community agent has performed his/her work.